Spectacular speculation : thrills, the economy, and popular discourse - Stäheli, Urs, 1966- (Stanford University Press, 2013)
Spectacular Speculation is a history and sociological analysis of the semantics of speculation from 1870 to 1930, when speculation began to assume enormous importance in popular culture. Informed by the work of Luhmann, Foucault, Simmel and Deleuze, it looks at how speculation was translated into popular knowledge and charts the discursive struggles of making speculation a legitimate economic practice. Noting that the vocabulary available to discuss the concept was not properly economic, the book reveals the underside of putting it into words. Speculation's success depended upon no.